Molecular Insights into the Effects of Rootstocks on Maturation of Blood Oranges - Lana, Giuseppe; Modica, Giulia; Las Casas, Giuseppina; Siracusa, Laura; La Malfa, Stefano; Gentile, Alessandra; Sicilia, Angelo; Distefano, Gaetano; Continella, Alberto (Horticulturae, 2021)
Rootstock choice has important effects on the horticultural and pathological traits of the citrus cultivars. Thus, the scion/rootstock combination can affect tree vigour, nutrition, and stress resistance; it can also have positive influences on the fruit quality traits. Although the study of rootstock effects has been a relevant research topic in citrus for many years, the main body of such study has been conducted at the biochemical level, while little effort has been directed to the determination of the rootstock influences at the molecular level. A comparative study of three combinations of scion and rootstock shows a positive correlation between the regulation of the fruit quality-related genes and the accumulations of bioactive compounds, as well as with acid degradation. Monitoring the anthocyanin accumulation during ripening shows the scion/rootstock combination can increase anthocyanin synthesis in the fruit, as well as vitamin C accumulation and acid degradation. Our results show that the rootstock genotype can exert important influences on citrus fruit quality by affecting gene expression in the scion. New insights into the molecular interactions between scion and rootstock may help unravel the systems through which rootstocks exert their influences on the regulatory networks in the scion, so as to influence relevant agronomic traits. This information should result in an improved rootstock breeding selection and definition of scion/rootstock combinations to enhance fruit quality traits.